2019
DOI: 10.1177/0003319719835637
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Normal Weight Central Obesity on Clinical Outcomes in Male Patients With Premature Acute Coronary Syndrome

Abstract: There is a lack of studies that evaluate the association between normal weight central obesity and subsequent outcomes in patients with premature acute coronary syndrome (ACS). We evaluated 338 consecutive male patients (aged ≤ 55 years) with premature ACS. The primary outcomes were all-cause mortality and major adverse cardiac and cerebrovascular events (MACCE). We compared the hazard ratios (HRs) in patients with and without normal weight central obesity using multivariable Cox proportional hazard models. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 56 publications
(74 reference statements)
1
20
0
Order By: Relevance
“…In particular, we found that subjects who maintained a "heavy" trajectory had the highest mortality, whereas those who remained on a "lean" trajectory had the lowest risk of death. Previous studies have demonstrated that a higher WHR trajectory pattern was one of the predictors of all-cause mortality [13,19]. In a prospective cohort from Scotland, a higher WHR predicted a higher all-cause mortality risk in female patients with HF [13]; however, the authors did not adopt a trajectory modeling approach to minimize reverse causation.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In particular, we found that subjects who maintained a "heavy" trajectory had the highest mortality, whereas those who remained on a "lean" trajectory had the lowest risk of death. Previous studies have demonstrated that a higher WHR trajectory pattern was one of the predictors of all-cause mortality [13,19]. In a prospective cohort from Scotland, a higher WHR predicted a higher all-cause mortality risk in female patients with HF [13]; however, the authors did not adopt a trajectory modeling approach to minimize reverse causation.…”
Section: Discussionmentioning
confidence: 94%
“…Several possible explanations have been proposed. First, patients with HFmrEF frequently suffer from multiple comorbidities, including hypertension, diabetes, obesity, coronary artery disease, and metabolic syndrome [13,19,37]. On account of these coexisting conditions, clinical trials have emphasized that an increase in WHR was a major contributor to a systemic proinflammatory state, which is involved in myocardial fibrosis, hypertrophy, and pathological remodeling, ultimately promoting left ventricular dysfunction [13,38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When we interpret the baseline characteristics using standard deviations (Table 1 in the paper by Wan et al 1 ), it seems that there is an issue with selection of the study population. For example, the normal BMI with low WHR group had some participants older than 55 years.…”
mentioning
confidence: 99%